Does The Lecturers’ Innovativeness Drive Online-Learning Adoption in Higher Education? A Study based on Extended TAM - Purwandari, diah; Saparudin, Mohamad; Wulan, Mulyaning; Akbari, Deni Adha; Kania, Azzura (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2024)
Adoption and intention to use online learning is a developing area of education research. Despite a large body of research on online learning acceptance, more is needed to know about the factors that impact lecturers' intentions to continue utilizing online learning. The purpose of this study is to give empirical evidence regarding the acceptance of online learning. The proposed model is based on the technology acceptance model (TAM). Several hypotheses were created using the TAM Model, utilizing lecturers' personal innovativeness as an external varaibel. This study used structural equation modeling (SEM-PLS) to investigate technology use among 180 lecturers. The findings suggested that the proposed model accurately predicted the desire to continue using e-learning. Lecturers' innovativeness had a significant impact on perceived usefulness (PU), perceived ease of use (PEOU), and intention to continue using e-learning. Perceived usefulness was the most important factor influencing the intention to continue using e-learning. PEO had a significant influence on PU and PU was able to mediate the relationship between LPI and PEO with CI. However, PEO did not.